Encyclopedia of tourism - Jafari, Jafar (Routledge, 2000)
In fewer than three hundred years tourism has become a global service industry of great economic, cultural and political importance. Published to critical acclaim, the Encyclopedia of Tourism - now available as a Routledge World Reference title - is the definitive one-volume reference source to this challenging multisectoral industry and multi disciplinary field of study.Comprising over one thousand entries, this volume has been written by an international team of contributors to provide a comprehensive guide to both the manifest and hidden dimensions of tourism. It explores.